2019
DOI: 10.3390/polym11020223
|View full text |Cite
|
Sign up to set email alerts
|

Silicone Implant Coated with Tranilast-Loaded Polymer in a Pattern for Fibrosis Suppression

Abstract: Pathologic fibrosis around silicone implants is problematic, and thus, these implants have been coated with a mixture of a biocompatible polymer and antifibrotic drug for sustained drug release to prevent fibrosis. However, a coating applied over an entire surface would be subject to mechanical instability as the implant would be severely crumpled for implant insertion. Therefore, in this work, we proposed localized, patterned coating dots, each composed of poly(lactic-co-glycolic acid) (PLGA) and tranilast, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…36 For example, a sustained Tra delivery system that is based on poly(lactic-co-glycolic acid) (PLGA) is capable of effectively preventing brosis. 37 Chien et al revealed that Tra-loaded microneedle (TMN) was effectively applied in a rabbit ear model to treat induced hypertrophic scars, and the expression of transforming growth factor-b, collagen-1, and a-smooth muscle actin proteins was reduced in TMN-treated HSs compared to the control. 38 Moreover, during the gradual formation and densication of the capsule, not only the migration and enrichment of broblasts are involved, but also the activation of broblasts and their polarization into myobroblasts are also crucial for capsular densication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 For example, a sustained Tra delivery system that is based on poly(lactic-co-glycolic acid) (PLGA) is capable of effectively preventing brosis. 37 Chien et al revealed that Tra-loaded microneedle (TMN) was effectively applied in a rabbit ear model to treat induced hypertrophic scars, and the expression of transforming growth factor-b, collagen-1, and a-smooth muscle actin proteins was reduced in TMN-treated HSs compared to the control. 38 Moreover, during the gradual formation and densication of the capsule, not only the migration and enrichment of broblasts are involved, but also the activation of broblasts and their polarization into myobroblasts are also crucial for capsular densication.…”
Section: Discussionmentioning
confidence: 99%
“… 36 For example, a sustained Tra delivery system that is based on poly(lactic- co -glycolic acid) (PLGA) is capable of effectively preventing fibrosis. 37 Chien et al revealed that Tra-loaded microneedle (TMN) was effectively applied in a rabbit ear model to treat induced hypertrophic scars, and the expression of transforming growth factor-β, collagen-1, and α-smooth muscle actin proteins was reduced in TMN-treated HSs compared to the control. 38 …”
Section: Discussionmentioning
confidence: 99%
“…The tissue slices were then mounted on glass slides, which were deparaffinized and rehydrated with xylene and ethanol for staining. To assess the fibrotic capsule thickness and collagen density, hematoxylin and eosin (H&E) and Masson’s trichrome (MT) staining were conducted following a previously reported protocol (Kim et al., 2019 ). The stained slides were evaluated by a professional pathologist (C. L.) using an optical microscope (ECLIPSE Ts2, Nikon, Minato, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, some studies were conducted using coating with a biocompatible polymer, poly(lactic-co-glycolic acid) (PLGA), and tranilast for the prevention of capsular contracture. The silicone implant was separately coated on all surfaces twice, with an interval of 30 min [ 59 ], and the silicone implant was coated with dots containing PLGA and tranilast [ 60 ]. Interestingly, the results showed that the combination of coated dots on silicone implants was more stable than loading drugs on all surfaces.…”
Section: Surface Modification Using Drugsmentioning
confidence: 99%
“…Afterward, the drug was released in a sustained manner for 14 days. The result revealed the benefit of using a PLGA matrix coated with dots, which released the drug in a diffusion-mediated manner [ 59 ].…”
Section: Surface Modification Techniquesmentioning
confidence: 99%